Intracellular Light‐Activation of Riboswitch Activity. Issue 9 (26th May 2014) - Walsh, Steven; Gardner, Laura; Deiters, Alexander; Williams, Gavin J.
Abstract By combining a riboswitch with a cell‐permeable photocaged small‐molecule ligand, an optochemical gene control element was constructed that enabled spatial and temporal control of gene expression in bacterial cells. The simplicity of this strategy, coupled with the ability to create synthetic riboswitches with tailored ligand specificities and output in a variety of microorganisms, plants, and fungi might afford a general strategy to photocontrol gene expression in vivo. The ability to activate riboswitches by using light enables the interrogation and manipulation of a wide range of biological processes with high precision, and will have broad utility in the regulation of artificial genetic circuits.